Business Information Systems - Rupnik, Bojan (Digitalna transformacija v logistiki in managementu oskrbovalnih verig, 2025)
Information systems have become an indispensable cornerstone of modern business operations, facilitating data management, process optimization, and informed decision-making. This abstract explores the pivotal role of information systems in business, with a specific focus on the pervasive influence of Enterprise Resource Planning (ERP) systems. ERP systems serve as integrated platforms that harmonize various business functions, streamlining processes and unifying data into a single, accessible repository. They empower organizations by providing centralized, real-time data, which aids in efficient resource allocation, cost reduction, and enhanced customer service. ERP systems are invaluable in driving cross-functional insights, fostering improved communication and collaboration, and ensuring data security and compliance. Moreover, these systems are a catalyst for strategic planning, offering the capacity for data-driven decision-making, predictive analytics, and long-term goal alignment. In essence, information systems, especially ERP, have revolutionized the way businesses operate, adapting to the ever-changing landscape of the digital age and serving as a cornerstone for achieving operational excellence and competitive advantage.